2013
DOI: 10.4314/tjpr.v11i6.4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pro-inflammatory Cytokines by Ethyl Acetate Extract of <i>Scrophularia striata</i>

Abstract: Purpose: To investigate the effect of ethyl acetate extract of S. striata on pro-inflammatory production by macrophages. Methods: Mouse peritoneal macrophages were cultured in solvent either alone or with 2 µg/ml lipopolysaccaride (LPS) with/without different doses of ethyl acetate extract of S. striata. Production of pro-inflammatory cytokines including interleukin 1β (IL-1β), tumor necrosis factor -α (TNF-α) and prostaglandin E2 (PGE2) were examined using ELISA. Results: Ethyl acetate fraction of S. striata … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…On the other hand, the antioxidant, anti-inflammatory and immunomodulatory activities of some species of Scrophularia have also been shown by several investigators (10,12,26); S. striata has been used to treat various inflammatory disorders (8,26,27). Our previous studies indicated the inhibitory effect of S. striata extract on pro-inflammatory mediator production by macrophages including nitric oxide, TNF-a, IL-1b and PGE2 production and also suppressive effects on matrix metalloproteinases in the Wehi-164 tumour cell line in vitro (8,9,13). In addition, antioxidant properties of compounds such as iridoide glycosides and phenylpropanoid esters isolated from S. buergeriana have been reported (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…On the other hand, the antioxidant, anti-inflammatory and immunomodulatory activities of some species of Scrophularia have also been shown by several investigators (10,12,26); S. striata has been used to treat various inflammatory disorders (8,26,27). Our previous studies indicated the inhibitory effect of S. striata extract on pro-inflammatory mediator production by macrophages including nitric oxide, TNF-a, IL-1b and PGE2 production and also suppressive effects on matrix metalloproteinases in the Wehi-164 tumour cell line in vitro (8,9,13). In addition, antioxidant properties of compounds such as iridoide glycosides and phenylpropanoid esters isolated from S. buergeriana have been reported (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 52%
“…Several species of Scrophularia have been used in folk medicine since ancient times, as a sedative and for treatment of illnesses such as scrophula, scabies, eczema, psoriasis and tumours. Our previous in vitro studies have demonstrated inhibitory effects of S. striata extract on nitric oxide production and on pro-inflammatory cytokine (including TNFa, IL-1b and PGE2) production by macrophages (8,9). In addition, anti-tumour, anti-inflammatory and immunomodulatory activities of some species of Scrophularia have been shown by other investigators (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 82%
“…S. striata has been used to treat various inflammatory disorders in animal models. Our previously studies indicated the inhibitory effect of S. striata extract on pro-inflammatory mediators production by macrophages including Nitric Oxide (NO), TNF-α, IL-1β and PGE2 and also suppressive effect on matrix metalloproteinases in Wehi-164 tumor cell line in vitro [9,10,25]. The results of this study showed that the treatment with S. striata extract (100 and 200 mg/kg) in OVA- sensitized /challenged mice significantly reduced the numbers of eosinophils and total inflammatory cells in the BALF comparing with OVA- sensitized /challenged mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several species of Scrophularia have been used since ancient times as sedative in folk medicine and for treatment of illnesses such as scrophulas, scabies, eczema, psoriasis and tumors [8]. Our previous studies in vitro demonstrated the inhibitory effect of S. striata extract on nitric oxide and pro-inflammatory cytokines including TNF-α, IL-1β and PGE2 production by macrophages [9,10]. In addition, the anti-inflammatory and immunomodulatory activity of some species of Scrophularia has also been shown by other investigators [11-13].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous findings demonstrated that Scrophularia species had the anti-cancer activity by induction of apoptosis and inhibition of matrix metalloproteinases, anti-asthmatic, neuroprotective, inhibitory effect on the nitric oxide and pro-inflammatory cytokines production. [3][4][5][6][7][8][9][10] In the present study we investigated the cytotoxic effect and induction of apoptosis of S. variegata in the MCF-7 human breast cancer cell line.…”
Section: Introductionmentioning
confidence: 99%